If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = v + -1(-3) Multiply -1 * -3 2 = v + 3 Reorder the terms: 2 = 3 + v Solving 2 = 3 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 2 + -1v = 3 + v + -1v Combine like terms: v + -1v = 0 2 + -1v = 3 + 0 2 + -1v = 3 Add '-2' to each side of the equation. 2 + -2 + -1v = 3 + -2 Combine like terms: 2 + -2 = 0 0 + -1v = 3 + -2 -1v = 3 + -2 Combine like terms: 3 + -2 = 1 -1v = 1 Divide each side by '-1'. v = -1 Simplifying v = -1
| -1/2x-5=15 | | 2x^2+5=5x^2-27 | | X+11+x+11=104 | | f/m=a | | 8-3(m-4)=2m | | w=7.5h | | 7x+7=6x+6 | | -16(x+1)=608 | | -3(2+n)=9 | | 41=8m-15 | | -265-(190)= | | (-4)+5/3 | | 18+3n=3+7+5n | | (x^3-16^2+64)/(x^3-8x^2) | | 9p-18=27 | | 2(x-3)=3(x+2)-3 | | 10(-11-4p)-2p=(-1-3p) | | (5x^3-9x^2+5)-(5-9x^2+5x^3)= | | -5(x-1)+x=6x-5 | | 7p+4=7-2p | | 7x+3(6x+3)=184 | | f(x)=x^2+6x-10 | | 2(675+80n)=2310 | | p/9-5=7 | | x/4-2=5/6+x-4/3 | | (10w-1)(10w+1)=20w | | 6y+2=3y-3 | | 14c-d-7= | | 2/x=-4 | | 3k+15=66 | | ((3x-1)/2)-((5x+4)/3)-((x+2)/8)=((2x-3)/5)-1/10 | | 36-y=-36 |